ANALISIS MANAJEMEN RISIKO PEMBIAYAAN PADA LEMBAGA KEUANGAN MIKRO SYARIAH (Studi Kasus pada Bank Wakaf Mikro Sunan Gunung Jati Ba’alawy) - Ella Wijayanti; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to analyze the risk management of financing in Islamic microfinance institutions with a case study at the Bank Wakaf Mikro Sunan Gunung Jati Ba'alawy Gunungpati and measure risk with a qualitative risk assessment. The establishment of the Bank Wakaf Mikro as a commitment from Otoritas Jasa Keuangan and the Government with the aim of expanding the provision of financial access to the community and empowering productive communities in the Islamic boarding school environment. Researchers use primary data obtained from interviews, legislation, management documents, and documentation that obtained during direct observation.The research method used in this study is a qualitative descriptive research method and data collection techniques through in-depth interview interviews in-depth interviews), direct observations, and documentation. The informant in this study amounted to 8 people. Interviews carried out are semi-structural interviews with managers of Islamic microfinance institutions, customers and community representatives.The results showed that the risk management of financing carried out by Islamic microfinance institutions is still weak despite having good financing and policy procedures. Qualitative risk assessment identifies 15 risks and is categorized into four levels of risk, neguligible, acceptable, undesirable, and unacceptable. Every risk level has a different risk response.